Pelatihan pemeriksaan prevention of disability (POD) kusta pada tenaga Kesehatan dan kader di Kabupaten Prabumulih - Nopriyati; Rusmawardiana; Argentina, Fifa; Deddy; Antonius, Cayadi Sidarta; Setiawan, Ivon; Veronica (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2023)
Leprosy is a chronic granulomatous infection caused by Mycobacterium leprae. Leprosy infects skin, mucosa and peripheral nerves causing loss of skin sensation with or without skin lesions. Clinical feature of leprosy is highly variable, and can resemble a variety of lesions present in other diseases. Differential diagnosis of skin lesions is so broad that it can lead to misdiagnosis. Based on data from the World Health Organization (WHO) in 2018, it was reported that the number of new cases of leprosy in the world was 210,671 cases, with a new case detection rate of 2.77 per 100,000 population. Indonesia is ranked third in the world as a country with the most new cases of leprosy after India and Brazil. Lack of knowledge of health workers and cadres affects the number of leprosy cases found. This community service activity was carried out with the aim of providing counseling regarding early leprosy examination to health workers and cadres in Prabumulih. The activity was coordinated by Dermatology, Venereology, and Aesthetics Department, Faculty of Medicine, Sriwijaya University, in collaboration with AR Bunda Hospital Prabumulih. At the end of the activity the participants had a better understanding of leprosy and the steps for early leprosy examination. This activity is useful for increasing the knowledge of health workers and cadres about leprosy and how to check for leprosy.